Interfacial variation in HfO2-based resistive switching devices with titanium electrodes under asymmetric bias operation. (9th February 2023) - Zhou, Kuan-Ju; Chen, Min-Chen; Chang, Ting-Chang; Lin, Shih-Kai; Wang, Yu-Bo; Zhang, Yong-Ci; Yen, Po-Yu; Shao, Kui-You; Huang, Hui-Chun; Huang, Jen-Wei; Sze, Simon M
Abstract: Resistance fluctuations are persistent and critical issues in memory device applications. In recent years, several investigations have been conducted to unravel such fluctuations to further improve the retention and endurance of random resistance access memory (RRAM). Elucidating the switching mechanisms and causes of delamination at the insulator/electrode interface during practical bias operations is thus essential for improving RRAM performance. In this work, we first investigated the changes at the Ti/HfO2 interface in the Ti/HfO2 /TiN RRAM device for consecutive bias operations. After the negative forming process and the following asymmetric bias operation conditions, the electrical output of the device decreased as a result of abnormal current degradation during iterative set/reset operations, during which the current high-resistance state (HRS) and low-resistance state (LRS) appeared to decrease. Transmission electron microscopy images and energy dispersive spectroscopy point data indicated that titanium oxides are formed at the Ti/HfO2 interface after asymmetric bias operation compared to the Ti/HfO2 interface of the pristine device, which provides direct evidence for validating the current degradation. In addition, to verify the influence of the electric fields on the devices during bias operation, we modulated the rising time of the set pulse triangle wavefront to further verify that the formation of TiO x depends on the amplitude of the electric field. Finally, the fitted current results indicate that the conduction mechanism after asymmetric bias operation in HRS and LRS is hopping conduction. Accordingly, a plausible physical model for bias operation in RRAM devices is proposed.